Towards the sustainable development of cultural landscapes through two case studies on different scale - Papageorgiou, Eirini (My University, 2016)
Since the beginning of the twentieth century the definition of Cultural Heritage has gradually expanded from the scale of individual monument to the scale of cultural landscapes. The broadening of the term has at the same time increased the complexity of the information originating from different domains and being on different scales and forms. In this context, the objectives as well as the challenges involved in the Cultural Heritage sector have become highly diversified, often leading to fragmented and less successful interventions which do not conform with the principles of Sustainable Development. Therefore Cultural Heritage and Sustainable Development should correlate with each another. Pursuing the achievement of sustainable models of development for cultural landscapes, this paper investigates how the factor of scale can act as a linkage between the fields of Cultural Heritage and Sustainable Development.
Keywords: Cultural heritage; Cultural landscapes; Heritage management; Network of settlements; River valleys; Scale factor; Strategic planning; Sustainable development